FILSAFAT EKONOMI ISLAM : PENDEKATAN SISTEM EKONOMI ISLAM, NILAI-NILAI DASAR, DAN INSTRUMENTAL - Siska Permata Sari Harahap; Darwin Multa Nasution; Thasya Virdinia; Budi Harianto (CV. ALIM'SPUBLISHING, 2024)
Islamic economic philosophy is the basis of an Islamic economic system which is based on Islamic teachings in achieving its goals. This article will outline the philosophical foundations of the Islamic economic system, explore the fundamental values that form the basis of Islamic economics, such as justice, togetherness, and blessing, and identify various economic instruments. The research method used is literature study and several other references. Islamic economic philosophy considers humans not as the center (anthropocentrism) but as servants of God who must serve and carry out the duties given by Him as managers (khalîfah). Therefore, in economic activities, it is very important to uphold the values of ownership, justice, freedom, balance, brotherhood and unity in accordance with religious teachings in order to form a harmonious order in personal, social and state life.